Inside Cover: Peptide‐Conjugated Long‐Lived Theranostic Imaging for Targeting GRPr in Cancer and Immune Cells (Angew. Chem. Int. Ed. 41/2020). Issue 41 (31st August 2020) - Wang, Wanhe; Wu, Ke‐Jia; Vellaisamy, Kasipandi; Leung, Chung‐Hang; Ma, Dik‐Lung
Abstract : An iridium(III)‐based long‐lived theranostic agent for gastrin‐releasing peptide receptor (GRPr) has been developed. In their Research Article on page 17897, C.‐H. Leung, D.‐L. Ma, and co‐workers describe an iridium(III) complex that selectively visualizes GRPr in living cancer cells while modulating the function of GRPr in immune cells. The complex serves as a versatile probe for unmasking the multifunctional roles of GRPr in living systems, while helping to accurately identify tumors and their biological characteristics.